Shademotion software for tree shade modeling, Version 5.0 - CGIAR Research Program on Forests, Trees and Agroforestry (2021)
The tool and a tutorial on how to use it are freely available on line and there is documentation of over 3500 users over the internet as well as 600 farmers and 169 extension staff across eight countries.